2014
DOI: 10.1016/j.resuscitation.2014.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cluster analysis for the identification of high-risk census tracts for out-of-hospital cardiac arrest (OHCA) in Denver, Colorado

Abstract: Background Prior research has shown that high-risk census tracts for out-of-hospital cardiac arrest (OHCA) can be identified. High-risk neighborhoods are defined as having a high incidence of OHCA and a low prevalence of bystander cardiopulmonary resuscitation (CPR). However, there is no consensus regarding the process for identifying high-risk neighborhoods. Objective We propose a novel summary approach to identify high-risk neighborhoods through three separate spatial analysis methods: Empirical Bayes (EB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 22 publications
1
56
0
Order By: Relevance
“…Introduced by Nassel et al (2014), we combined three separate analytical spatial clustering methods to identify areas that were hot spots for sepsis mortality. 12 We categorized county-level sepsis clustering into three groups: strongly clustered, moderately clustered, and non-clustered. We considered a county to be strongly clustered if it was identified as high risk or sepsis hot spot using all three geospatial metrics (5th quartile of Empirical Bayes (EB) smoothed sepsis mortality rates, high-high cluster using Local Moran's I, and sepsis hot spot as defined by Getis-Ord Gi*).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Introduced by Nassel et al (2014), we combined three separate analytical spatial clustering methods to identify areas that were hot spots for sepsis mortality. 12 We categorized county-level sepsis clustering into three groups: strongly clustered, moderately clustered, and non-clustered. We considered a county to be strongly clustered if it was identified as high risk or sepsis hot spot using all three geospatial metrics (5th quartile of Empirical Bayes (EB) smoothed sepsis mortality rates, high-high cluster using Local Moran's I, and sepsis hot spot as defined by Getis-Ord Gi*).…”
Section: Methodsmentioning
confidence: 99%
“…12 We further categorized the EB smoothed sepsis mortality rates into quintiles, and we defined counties as high-risk if the EB sepsis mortality rates were in the top quintile. Second, we used Local Indicators of Spatial Autocorrelation 13 to measure similarity between counties and calculate values both within and across geographic boundaries, additionally identifying spatial outliers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were geocoded with ArcGIS (version 9.3; Environmental Systems Research Institute Inc., Redlands, CA) and Geoda software (http://geodacenter.asu.edu), and spatial analysis methods were used to identify high-risk census tracts. 16 …”
Section: Methodsmentioning
confidence: 99%
“…In accordance with previous research, 11,12,15 we identified 5 neighborhoods in Denver in which the incidence of out-of-hospital cardiac arrest was 2 to 5 times higher than the median for the county and rates of bystander CPR were below average. 16 These high-risk neighborhoods were composed of primarily Latinos and lower socioeconomic status residents.…”
mentioning
confidence: 99%